A Carboniferous Bentonite Province in New South Wales (The Australasian Institute of Mining and Metallurgy, 1965)
Recently discovered Carboniferous bentonites are variable in charadeI and thickness, but being altered aeolian, ash-fall tuffs, they are probably extensive. Most are the Ca-montmorillonite type without the natural swelling characteristics of the Wyoming deposits, but their situation, thickness, and response to beneficiation through cation exchange may give them some potential as sources of future economic deposits.INTRODUCTIONLoughnan and See (1959) gave an account of bentonites and fuller's earth deposits of New South Wales. The most likely potential industrial sources were those occurring in the uppermost formations of the Newcastle and Singleton Coal Measures (Permian) in the Hunter Valley and deposited during epochs not marked by strong contemporary vulcanicity.One feature of the record of known occurrences at that time was the absence of bentonites from the thick volcanic sequences of the Carboniferous, but since this paper appeared, many bentonite beds have been discovered by the writer in the Carboniferous facies formerly known as the "Kuttung Series".The purpose of this contribution is to report briefly on the occurrence, genesis, mineralogy, and economic potential of these deposits which augment possible sources of bentonite near major industrial centres on the eastern seaboard.The potential world demand for bentonite would increase markedly with the trend to pelletization in the steel industry, if its use in this field became more general. More detailed mineralogical studies will be presented in later publications.STRATIGRAPHIC DISTRIBUTIONBentonite occurs at irregular intervals throughout a thick sequence of dominantly continental, plant bearing strata...